Characterization of textile-grade carbon fiber polypropylene composites. Issue 6 (July 2021) - Yeole, Pritesh; Alwekar, Shailesh; Veluswamy, N Krishnan P; Kore, Surbhi; Hiremath, Nitilaksha; Vaidya, Uday; Theodore, Merlin
In this work, we consider low-cost carbon fiber produced with a textile-grade precursor. The objective of the study is to investigate textile-grade carbon-fiber-reinforced-polypropylene composites (TCF-PP) from compounded pellets for mechanical and thermal characterization. Four sets of pellets with 1%, 5%, 10%, and 15% reinforcement were manufactured using textile-grade carbon fiber (TCF) and polypropylene (PP) by twin-screw compounding. The addition of TCFs through gravimetric feeder directly in the extruder resulted in lower fiber content; however, side feeder has shown good potential. The pellets were further processed in extrusion compression molding to manufacture plaques. An increase in fiber loading has a negligible effect on fiber attrition as fiber length distribution variation between 1% and 15% reinforced pellets was very small. The addition of TCFs in PP showed a significant improvement in mechanical properties. The tensile strength and modulus of the composite were 26% and 161%, respectively, improved by the addition of 10 wt% TCF. Similar results were observed in the flexure test. However, the impact properties were reduced by 25.54% by the addition of 15% TCF.